2015
DOI: 10.1107/s2056989015006775
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of 1-[(Z)-2-phenylhydrazin-1-ylidene]naphthalen-2(1H)-one

Abstract: In the title compound, C16H12N2O, the dihedral angle between the planes of the benzene ring and naphthalenone ring system is 1.89 (8)°; an intra­molecular N—H⋯O hydrogen bond occurs between the imino group and the carbonyl group. In the crystal, mol­ecules are linked by weak C—H⋯π inter­actions into supra­molecular chains propagating along the [01-1] direction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The molecule adopts zwitterionic form (i.e. proton from the hydroxyl in the naphthol group is transfer to the azo-group), the two groups are linked by an intramolecular N1-H1…O1 hydrogen bond, enclosing an S(6) ring motif [43,44]. The same hydrogen atom participates in a second intramolecular hydrogen bond N1-H1…O2 enclosing another S(6) ring motif (Fig.…”
Section: Xrd-packing and Hsamentioning
confidence: 99%
“…The molecule adopts zwitterionic form (i.e. proton from the hydroxyl in the naphthol group is transfer to the azo-group), the two groups are linked by an intramolecular N1-H1…O1 hydrogen bond, enclosing an S(6) ring motif [43,44]. The same hydrogen atom participates in a second intramolecular hydrogen bond N1-H1…O2 enclosing another S(6) ring motif (Fig.…”
Section: Xrd-packing and Hsamentioning
confidence: 99%
“…A search of the Cambridge Structural Database (CSD; Version 2023.2.0, last update September 2023; Groom et al, 2016) for 1-phenylazo-2-naphthol derivatives revealed that numerous azo-2-naphthol compounds with similar structures have been synthesized using various aromatic primary amines. Benosmane et al, 2013), 1-[(E)-2-(5-chloro-2 hydroxyphenyl) hydrazin-1-ylidene]naphthalen-2(1H)-one (UVIDOV; Bougueria et al, 2021), OGUXAP01, OGUXAP02 and OGUXAP03;Gilli et al, 2002), (E)-1-[2-(3-nitrophenyl)hydrazinylidene]naphthalen-2(1H)-one (FIFCEG; Benaouida et al, 2023), 1-(phenylazo)-2-naphthol (JARPEX; Olivieri et al, 2002), (Z)-1-(2-phenyldiazen-2-ium-1-yl)naphthalen-2-olate (TIFTEJ01; Benosmane et al, 2015). All these compounds belong to the azo dyes family and share a common base structure -a benzene ring and a naphthalene ring system linked with an oxygen in the ortho position relative to the azo group.…”
Section: Database Surveymentioning
confidence: 99%
“…In the case of 1-phenylazo-2-naphthol derivatives, a strong hydrogen bond enhanced by resonance is established, inducing the azo (OH) ! hydrazo (NH) tautomeric displacement (Benosmane et al, 2015;Bougueria et al, 2014). This is directly connected with the presence of at least one protic donor group in conjugation to the azo bridge (2-naphthol) (Antonov, 2016).…”
Section: Chemical Contextmentioning
confidence: 99%